SPAWNING OF BLACK GHOST KNIFEFISH, Apteronotus albifrons WITH DIFFERENT SEX RATIOS - Fajar Maulana; Dinar Tri Soelistyowati; Muhammad Fadlan Furqon (Indonesian Aquaculture Journal, 2021)
Black ghost knifefish, Apteronotus albifrons, is a South America-introduced ornamental fish species that has been widely cultivated in Indonesia. Some farmers breed this fish with different sex ratios, but the optimum sex ratio remains unclear. This study aimed to evaluate the spawning behavior and reproductive performance of black ghost knifefish with different sex ratios. The treatments in this study were arranged in a completely randomized design consisting of different sex ratios between males and females, namely: A (one male : three females), B (two males : three females), and C (three males : three females). Each treatment was done in triplicate. The broodstock were maintained in an aquarium (80 cm x 40 cm x 40 cm) and fed with bloodworm twice a day. The water was changed every day as much as 60% of the total volume. During the experiment, the parameters of spawning behavior, number of fish spawning, number of eggs, fertilization rate, hatching rate, and daily spawning frequencies were observed. The observation was done for seven days. The study results showed that black ghost knifefish spawned at night (11 pm - 2 am). The mating and spawning occurred between one male and one female. Competition between males was observed in the treatments indicated by aggressive movements of a male toward the others, such as sudden approaching, chasing, and driving away the others. Fish in treatment-B spawned consistently from day-1 to day-5. Fish in treatment-A spawned from day-2 to day-4, while fish in treatment-C spawned only on day-7. The reproductive performance parameters showed no significant difference in all treatments except the hatching rate parameter of treatment-B. The study concludes that better reproductive performance of black ghost knifefish, A. albifrons can be achieved with a spawning ratio of two males and three females. Further research on individual and mass spawning methods with the best spawning ratio of the fish is required.